Sensitive Spectrophotometric Determination of Deltamethrin Using Leuco Malachite Green in Environmental Samples - Nirmal, Mamta; Rai, Manish Kumar; Patel, Vindhiya; Khatoon, Raisa; Wani, Kalpana; Rai, Joyce (Asian Journal of Chemistry, 2015)
A spectrophotometric method for the determination of deltamethrin is reported. The method is based on hydrolysis of deltamethrin to form dibromochrysanthemic acid and phenoxybenzaldehyde cyanohydrin then phenoxybenzaldehyde cyanohydrin on further hydrolysis releases cynide which after bromination form cynogen bromide which reacts with potassium iodide-potassium iodate mixture in the presence of leuco malachite green to form a greenish blue coloured complex which is soluble in 70 % alcohol. The complex shows maximum absorbance at 620 nm. Beer’s law obeyed over the concentration range of 10-50 μg in a final solution volume of 10 mL. The molar absorptivity of the coloured system is 7.72 × 104 L mol-1 cm-1 and Sandell’s sensitivity is 1.0 × 10-3 μg cm-2. The reproducibility assessed by carrying out seven days replicate analysis of a solution containing 10 μg of deltamethrin in a final solution volume of 10 mL. The standard deviation and relative standard deviation for the absorbance value were found to be 1.53 × 10-3 and 1 %, respectively. The proposed method is free from the interference of other toxicants. The analytical parameters were optimized and the method was applied to the determination of deltamethrin in various environmental samples.